Pengaruh Kualitas Produk, Word Of Mouth (Wom) dan Citra Merek Terhadap Keputusan Pembelian Produk - Ratna Sintya Handayani Siregar; Sumaryanto Sumaryanto; Riska Fii Ahsani (Universitas 45 Surabaya, 2024)
The aim of this research is to analyze the effect of product quality, word of mouth (WOM) and brand image on product purchasing decisions. The population in this study were all consumers who purchased Karanganyar love brownies for the 2024 period with a sample size of 100 respondents determined using purposive sampling technique. The results of the analysis show that product quality has an insignificant effect on purchasing decisions for consumers of Brownies Cinta Karanganyar, word of mouth has a significant effect on purchasing decisions for consumers of Brownies Cinta Karanganyar and brand image has a significant effect on purchasing decisions for consumers of Brownies Cinta Karanganyar. The F test results show the calculated F value of 28,720 with a p value (significance value) of 0.000 <0.05, so Ho is rejected and Ha is accepted. The test result of the coefficient of determination (adjusted R2) is 0.457, meaning that the magnitude of the contribution of the independent influence of X1 (Product Quality), X2 (Word of Mouth) and X3 (Brand Image) on Y (Purchase Decision) is 45.7%.